Que faire de la diversité ? Hôpital et École face aux discriminations ethno-raciales - Olivier Cousin (Recherches en Éducation)
The article is based on extensive research dealing with the experience of discrimination. School and public hospital were two of the theaters in which the survey was conducted. Two institutions that historically have been protected by discrimination by displaying their universalism. The school has to deal, in theory, only with the students, the hospital only with the patients, and each of these institutions remains deeply attached to the republican principle. Yet today, these institutions experience and face discrimination and acknowledjement of diversity differently. To understand these differences, we must remember how the relationship between universalism and particularism plays in the hospital and at school. It is at the foundation of medical practice, but school has rejected historically this opportunity. Racial discrimination remains marginal in the hospital because its organization is based on combination of an objective and rational treatment of the patient and the individualization of its management. In school, they are not necessarily more important. But the fear of discrimination contaminate the institution because of the combined effects of school sorting and spatial segregation , and discomfort with regard to the place given to the management of diversity.